(untitled) (Al-Qamar, 2021)
"Ilm-e-Jarh-o-Ta’dil" is the knowledge in which the authenticity of the narration of a hadith is discussed, whether it is just, well-ordered or their imperfections. The authenticity of a hadith depends on the condition of the narrator, and the authenticity of these narrations is evident from the testimony of the scholars. This information and news of the Hadith scholar (Muhaddithin) is called " Ilm-e-Jarh-o-Ta’dil ". We have received the hadith of the Prophet through narration. The authenticity of a hadith is the first step towards knowing the validity of a hadith, so the scholars of hadith have stated that in order to accept the narrations of the hadith; certain conditions are necessary. The compilation of this skill form in book form dates back to almost the second century. In the first three hundred years, Shaykh Muhammad Ibn Hasan al-Saghani raised the standard of publishing the knowledge of Hadith, in the second three hundred years, Shaykh Muhammad Ibn Tahir al-Hindi Patni took the lead in publishing the science of hadith, and in the third three hundred years, Shaykh Abdul Hai Lucknow Played an important role in the publication of Hadith. This second period of publication of knowledge of Hadith is called the period of Mughal Empire Muhaddithin has made full use of the books containing your knowledge of Hadith, which is like a golden chapter. I have been presented.